Estudo de agentes alquilantes para o cardanol hidrogenado - Sancho, Emmanuelle de Oliveira (2005)
This work has investigated the hydrogenated cardanol (3-PDP) alkylation’s process through the use of the following alkylating agents: methyl terc-butyl ether, cyclehexanol, isoamilic alcohol and glycerol. The alkylation process using alcohol was accomplished with the use of zinc chloride as catalyst in the range of temperature of 70 to 120 °C. The reaction was conducted during 24 hours with the conversion yields checked up every hour. This check up was done through the use of thin layer chromatography and it was noticed the conversion of hydrogenated cardanol (3-PDP) into an alkylated product. At the end of each process, the products were properly purified and analyzed by the use of gas chromatography coupled with mass spectrometry (GC/MS). The yields related to the use of cyclehexanol, isoamylic alcohol and glycerol were considered insignificant. As far as the use of methyl terc-butyl ether (MTBE) is concerned as an alkylating agent for hydrogenated cardanol, two routes were researched: in the first, it was used heterogeneous catalysis by means of an acid resin AMBERLYST 35WET ® type. For this purpose it was constructed a fix bed reactor, in which hydrogenated cardanol solution in MTBE was percolated in order to convert cardanol into an alkylated product (6-terc-butyl 3-pentadecylphenol). Experiments were done at temperatures of 50, 80, 100 and 120 °C, in a fix bed reactor. The hydrogenated cardanol solution in MTBE has shown a rate of 1:2000, varying the flow between hydrogenated cardanol and MTBE 200mL/h. The maximum conversion yield obtained was 22%, among several experiments done. The strong acid character of this catalyst was responsible by the breaking up of the hydrogenated cardanol into several undesirable byproducts. In the second route, MTBE was used to alkylated hydrogenated cardanol in a stirred vessel reactor using sulfuric acid as catalyst in a rate of 1:1 cardanol/sulfuric acid, at a temperature of 60 °C, for a 48 hours period. In this case, the results showed a relative technical significance, with conversion yields up to 70%.